History of the literary cultures of East-Central Europe. junctures and disjunctures in the 19th and 20th centuries - Cornis-Pope, Marcel; Neubauer, John, 1933-2015 (Comparative history of literatures in European languages, 2010)
Types and stereotypes is the fourth and last volume of a path-breaking multinational literary history that incorporates innovative features relevant to the writing of literary history in general. Instead of offering a traditional chronological narrative of the period 1800-1989, the History of the Literary Cultures of East-Central Europe approaches the region's literatures from five complementary angles, focusing on literature's participation in and reaction to key political events, literary periods and genres, the literatures of cities and sub-regions, literary institutions, and figures of rep.